Clustering method for spread pattern analysis of corona-virus (COVID-19) infection in Iran - Azarafza, Mehdi; Azarafza, Mohammad; AkgÃ¼n, Haluk (Yayasan Ahmar Cendekia Indonesia, 2021)
The COVID-19 is outbreak from China and infected more than 131,652 people and caused 7,300 deaths in Iran. Unfortunately, the infection numbers and deaths are still increasing rapidly which has put the world on the catastrophic abyss edge. Application of data mining to perform pattern recognition of infection is mainly used for preparing the spread mapping which considered in this work for spatiotemporal distribution assessment and spread pattern analysis of corona-virus (COVID-19) infection in Iran